Double-Pass Multiple-Plate Continuum for High-Temporal-Contrast Nonlinear Pulse Compression - Chen, Bo-Han; Su, Jia-Xuan; Guo, Jhan-Yu; Chen, Kai; Chu, Shi-Wei; Lu, Hsuan-Hao; Lu, Chih-Hsuan; Yang, Shang-Da (Frontiers in Photonics, 2022)
We propose a new architecture, double-pass multiple-plate continuum (DPMPC), for nonlinear pulse compression. In addition to smaller footprint, a double-pass configuration is designed to achieve substantial bandwidth broadening without incurring noticeable higher-order dispersion, thus improving the temporal contrast over those of traditional single-pass geometry when only quadratic spectral phase can be compensated. In our proof-of-concept experiment, 187 μJ, 190-fs Yb-based laser pulse is compressed to 20 fs with high throughput (75%), high Strehl ratio (0.76) and excellent beam homogeneity by using DPMPC. Subsequently generated octave-spanning spectrum exhibits a significantly raised blue tail compared with that driven by pulses from a single-pass counterpart.